Analisis Pelaksanaan Sistem Akuntansi pada APBDes Pemerintah Desa di Kecamatan Banjarharjo Kabupaten Brebes - Rais Puji Rahayu; Roni Roni; Andi Yulianto; Titi Rahmawati; Slamet Bambang Riono (Journal of Accounting and Finance (JACFIN), 2019)
The village budget is one of the things that must be considered to realize good governance in the village. The purpose of this study is to determine the readiness, planning, implementation, administration, reporting, and accountability of the village government in Banjarharjo District, Brebes Regency in managing village finances through Siskuedes. The method used in this study is descriptive quantitative, namely analyzing the implementation of the APBDes accounting system. The results showed that, 1) the readiness of village officials in the accountability of village fund management showed a percentage of 99.38%; 2) planning apbdes with several indicators, namely by the village head and improved to determine the draft village regulation on APBDes into village regulations reaching 100% in each indicator; 3) the implementation of the APBDes shows a percentage of 96.15%, namely village expenditures excluding binding employee expenditures and office operations stipulated in the village head regulation; 4) accountability for apbdes administration shows a percentage of 100% in each indicator; 5) accountability for reporting the use of APBDes shows a percentage of 100%; 6) accountability of APBDes accountability shows a percentage of 100% in each indicator.